The Law of Motion in Determining the Tension of the Cocoon Thread - Khalima Umurzakova; Khalimaxon Alimova; Sevara Holdarova (Research Parks Publishing LLC, 2022)
is studied process removing threads from a cocoon surface at unwinding and influencing factors on change of speed of unwinding. Also it is studied dynamics and laws raw silk winding on a reel, it is presented change of depth of immersing, an immersing corner, and factor of resistance from cocoon radius. The equation and calculations on cocoon movement on the viscous liquid environment are resulted theoretical. Constant factors, and, b and c are presented at various values of factor of viscosity n. From the analysis of tabular data follows, that with parametre growth n the attenuation factor a grows, other parameters b and c at first with growth n at first quickly grow and further vary slightly.